Validity and Reliability of Students Perceptions on OBE Approach in Malaysian VC Using Rasch Model - Shuhada Abdul Raof; Farid Kamil Zamzuri; Mohammad Hafiz Salleh; Aede Hatib Musta’amal (Journal of Innovation in Educational and Cultural Research, 2021)
This pilot study aims to produce empirical evidence regarding the validity and reliability of instrument of the perception of vocational college diploma students towards the Outcome Based Education (OBE) approach. Validity and reliability were analysed using Rasch Model Measurement assisted by Winsteps 3.72 software. This research instrument contained 26 items and was distributed to 60 diploma students of vocational college at the Northern Zone. Validity analysis of the instrument was done through four functional testings. For reliability and separation of respondents, it was found that the individual reliability value was 0.91, while that for items demonstrated an item value of 0.94 and item separation index of 3.90. Results from the analysis of polarity item found that 25 items had a positive PMC value between 0.52-0.83. Meanwhile, analysis on item fit found 23 items with an outfit mean-square value between 0.41 and 1.24. This situation suggested three items that require attention. In the analysis on local dependence that determines dependent items based on the standardised residual correlation value, it was shown that the correlation value for the items used did not overlap with that of other items. These findings provided the evidence that the instrument of perception of vocational college diploma students on OBE approach has a high level of validity and reliability to be used in actual studies.